Epidermal growth factor and potent phorbol tumor promoters induce epidermal growth factor receptor phosphorylation in a similar but distinctively different manner in human epidermoid carcinoma A431 cells. - Shintaro Iwashita; Colin Fox (1984)
12-O-tetradecanoylphorbol 13-acetate; TPCK, tosylphenylalanyl chloromethyl ketone; PDBu, phorbol 12,13-